FACTORS THAT AFFECT OUR SPIRITUAL WORLD IN MODERN TIMES AND THEIR SOCIAL AND PHILOSOPHICAL ANALYSIS - Abdullayeva, N.A. (International Journal of Research -GRANTHAALAYAH, 2017)
Today, there is a great need for the revision of the system of spiritual values that constitute the cultural basis of every society from the public practice and high intellect to which humanity has acquired, and re-evaluating their role in human life. Thus, the globalization process in the world raises the problem of spiritual values and creates the need for scientific-philosophical analysis of social-spiritual aspects of free society building. It should be noted that the spiritual world of the Azerbaijani people, which has repeatedly encountered the trials of the history with an interesting and rich history in the crossroads of different religions and cultures, has emerged, formed and developed on a rich foundation, grown into its national-psychological trajectory. It is very important to study the universality inherent in the national-cultural and spiritual systems, cultures for the philosophical view of Azerbaijan in modern times.